KAJIAN PERKEMBANGAN AKTIFITAS KOMERSIAL DI KAWASAN KAMBANG IWAK PALEMBANG - Endang Sri Lestari (Jurnal Tekno Global, 2021)
Kambang Iwak Palembang is one of the most public Open Space Open Space in Palembang city. This public space can be one of the potential objects to improve the quality of life of the community and also stimulate the creativity of the community. Its strategic location beraa in the middle of the city makes this area easy to access from all directions and supported by public transportation available to meuju to this area. Kambang Iwak Palembang, is one of the most visited by the people of Palembang, especially on holidays. The existence of a commercial function in a green open space environment in addition to providing attractiveness also provides financial benefits to the manager who works with the government. The existence of this function in the region such as Kambang Iwak Palembang, in addition to bring a positive impact but also will give birth to other questions. The purpose of this study is further, whether the excess function of commercial Area as a center of culinary tourism in the Kambang Iwak Palembang region will increasingly support the climate of the Public Sphere well in the region, or vice versa it causes new problems in the implementation. The method used in this research is descriptive qualitative method. The results of the discussion that will be achieved in this research is to know the positive impact of additional commercial area Kambang Iwak area such as the increasing number of visitors and make this area as the icon of culinary tourism in the city of Palembang.Keywords : Open Space Green, Public Space, Commercial Area.